Multifunctional magnetically removable nanogated lids of Fe3O4-capped mesoporous silica nanoparticles for intracellular controlled release and MR imaging - Chen, Po-Jung; Hu, Shang-Hsiu; Hsiao, Chi-Sheng; Chen, You-Yin; Liu, Dean-Mo; Chen, San-Yuan (My University, 2011)
In this study, a novel nanocarrier (MSN@Fe3O4) is constructed using a facile technology by capping mesoporous silica nanoparticles (MSN) with monodispersed Fe3O4 nanoparticles through chemical bonding. The chemical links provide adhesion, which permits the magnetic nanoparticles, as nano-caps, to efficiently cover the mesoporous pores on the mesoporous silica matrix and be tightly bonded with the matrix surface. Without magnetic stimulus, none or only a negligible amount of the drug can be released from the MSN@Fe3O4. However, when subjected to an external controllable magnetic field, a quantity of nano-caps can be remotely and precisely removed, giving tunable release profiles for an anticancer drug, (S)-(+)-camptothecin (CPT), with various dosages depending upon the strength and time period of magnetic induction. The transverse relaxivity (r(2)) of the MSN@Fe3O4 nanocarriers was measured to be about 121.57 s(-1)mM(-1) Fe, which is larger than that for the reported mesoporous silica nanoparticles decorated with magnetite nanocrystals. Therefore, MSN@Fe3O4 nanocarriers could perform well as T-2-type MR contrast enhancement agents for cell or molecular imaging. In addition, the MSN@Fe3O4 nanocarriers also demonstrate fairly high cell uptake efficiency. Together with its versatile magnetic manipulation, this new type of MSN@Fe3O4 nanosystem can be considered as a new class of multifunctional nanodevice, with combined tunable drug release and nanoimaging modalities for a variety of biomedical uses.